Work engagement pada anggota komunitas: Bagaimana peranan job crafting dan psychological capital? - Erica Dica Pratiwi; Diah Sofiah; Yanto Prasetyo (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to determine the relationship between job crafting and psychological capital with work engagement among members of the Young Entrepreneur Club community. This research is a type of quantitative research using multiple regression data analysis research. The subjects of this study were 70 active members of the Young Entrepreneur Club in Surabaya. The data collection method was carried out by distributing questionnaires. The results obtained show a coefficient of 13,107 with significance = 0.000 < 0.01, which means that there is a positive relationship between job crafting and psychological capital with work engagement. This shows that the higher the job crafting and psychological capital of the members, the higher the work engagement. The effective contribution is 7.72%, while 71.93% work engagement is influenced by other predictor. Keywords: Job Crafting, Psychological Capital, Work Engagement, Young Entrepreneur Club Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara job crafting dan psychological capital dengan work engagement pada anggota komunitas Young Entrepreneur Club. Penelitian ini merupakan jenis penelitian kuantitatif dengan menggunakan penelitian analisis data regresi berganda. Subjek penelitian ini sebanyak 70 anggota aktif Young Entrepreneur Club di Surabaya. Metode pengumpulan data yang dilakukan melalui penyebaran kuesioner. Adapun hasil yang diperoleh menunjukkan nilai koefisien 13.107 dengan signifikasi = 0,000 < 0,01 yang artinya terdapat hubungan positif antara job crafting dan psychological capital dengan work engagement. Hal ini menunjukkan bahwa semakin tinggi job crafting dan psychological capital pada anggota maka semakin tinggi work engagement. Sumbangan efektif sebesar 7,72%, sementara 71,93 % work engagement dipengaruhi oleh prediktor lain. Kata kunci : Job Crafting, Psychological Capital, Work Engagement, Young Entrepreneur Club